Study on the AFM Force Curve Common Errors and Their Effects on the Calculated Nanomechanical Properties of Materials - Almasi, D.; Sharifi, R.; Kadir, M.R.A.; Krishnamurithy, G.; Kamarul, Tunku (Hindawi Publishing Corporation, 2016)
The atomic force microscope (AFM) force curve has been widely used for determining the mechanical properties of materials due to its high resolution, whereby very low (piconewton) forces and distances as small as nanometers can be measured. However, sometimes the resultant force curve obtained from AFM is slightly different from those obtained from a more typical nanoindentation force curve due to the AFM piezo’s hysteresis. In this study the nanomechanical properties of either a sulfonated polyether ether ketone (SPEEK) treated layer or bare polyether ether ketone (PEEK) were evaluated via AFM nanoindentation and a nanomechanical test system to probe the possible error of the calculated nanomechanical properties due to the AFM piezo’s hysteresis. The results showed that AFM piezo’s hysteresis caused the error in the calculated nanomechanical properties of the materials.